Experimental device and method for testing dynamic characteristics of zirconium alloy femtosecond laser modified surface

By designing an experimental device for measuring the dynamic characteristics of femtosecond laser modified surface of zirconium alloy, the problem of changes in heat transfer performance caused by deposition of microstructures in actual environment is solved, and an effective evaluation of dynamic heat transfer characteristics and fouling deposition characteristics is achieved, guiding process optimization.

CN119643627AActive Publication Date: 2025-03-18NUCLEAR POWER INSTITUTE OF CHINA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411520471.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

In actual use environment, the microstructure of the femtosecond laser modified surface of zirconium alloy is easily deposited by ions or impurities in the solution environment, resulting in microstructure failure and changes in heat transfer properties. It is difficult for the prior art to effectively measure its dynamic characteristics.

Method used

A dynamic characteristic testing experimental device is designed to determine the heat transfer coefficient, nucleation quantity and weight changes of the femtosecond laser modified surface of zirconium alloy by timed acquisition of temperature values, taking bubble nucleation images and recording weight values ​​within the preset period, thereby evaluating its dynamic heat transfer characteristics and dirt deposition characteristics.

Benefits of technology

Effective measurement of the dynamic heat transfer characteristics and fouling deposition characteristics of the femtosecond laser modified surface of zirconium alloy is achieved, providing a basis for evaluating the long-term use effect of the modified surface and guiding the iterative optimization of the laser modification process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643627A_ABST
    Figure CN119643627A_ABST
Patent Text Reader

Abstract

The invention discloses a dynamic characteristic test experiment device and method for a zirconium alloy femtosecond laser modified surface, and the device can provide a real environment of a simulation test material in a nuclear reactor fuel assembly system. The temperature values of at least two temperature detection devices are regularly acquired in a preset period, the bubble nucleation image of the surface of the test material is regularly shot through the visual window, and the weight value of the test material is recorded, so that the heat transfer coefficient, the nucleation number and the weight change of the test material are determined; therefore, the dynamic characteristics of the zirconium alloy femtosecond laser modified surface including the dynamic heat transfer characteristic and the dirt deposition characteristic are determined, the iterative optimization of the laser modification process can be known subsequently, and the real effect of the modified surface after long-term use can be evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of dynamic characteristic testing, and in particular to an experimental device and method for dynamic characteristic testing of a zirconium alloy femtosecond laser modified surface. Background Art

[0002] In nuclear reactor fuel assembly systems, zirconium alloys with good radiation resistance are mostly used for the cladding of nuclear fuel elements. In order to improve the local heat-carrying capacity of the nuclear reactor core, the heat transfer effect of zirconium alloys has been paid much attention. Femtosecond laser modification technology can prepare microstructures on the metal surface. Figure 1 A schematic diagram of the microstructure of a zirconium alloy femtosecond laser modified surface is shown as an example. On the one hand, the microstructure is conducive to the increase of the contact area, and on the other hand, the microstructure can serve as a cavity for the formation of bubbles, thus having the effect of improving the heat transfer capacity.

[0003] However, in actual use, the microstructure formed by femtosecond laser is easily deposited by ions or impurities in the solution environment, causing the microstructure to gradually be filled and fail. In this dynamic process, the heat transfer performance of the femtosecond laser-modified surface will also change accordingly. Therefore, it is very important to measure the dynamic characteristics of heat transfer and dirt on the surface of zirconium alloy femtosecond laser modified surface. Therefore, how to determine the dynamic characteristics of zirconium alloy femtosecond laser modified surface has become a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0004] In view of this, the present application provides an experimental device for testing the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified, which can provide a simulation of the real environment in which the test material is located in a nuclear reactor fuel assembly system, and determine the heat transfer coefficient, nucleation quantity and weight change of the test material by regularly acquiring the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material, thereby determining the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified including dynamic heat transfer characteristics and dirt deposition characteristics, so as to facilitate the subsequent iterative optimization of the laser modification process and evaluate the real effect of the modified surface after long-term use.

[0005] According to one aspect of the present application, a dynamic characteristics test experimental device for a zirconium alloy femtosecond laser modified surface is provided, comprising: a shell, a support frame, a heating component and a pressure cover, wherein the support frame, the heating component and the pressure cover are located inside the shell;

[0006] The heating assembly comprises a heating core and a heating element, wherein the heating element is arranged inside the heating core, a test material is arranged on the upper end of the heating core, and the test material is attached to the upper end of the heating core through the gland; at least two temperature detection devices are arranged inside the heating core and between the heating element and the test material according to the heat transfer direction of the heating element; the heating core is connected to the shell through the support frame;

[0007] The housing is provided with a visual window, and the visual range of the visual window includes the test material.

[0008] In some embodiments, the heating core includes a first component and a second component connected to the first component, and the heating element is arranged in the first component; the test material is arranged at the upper end of the second component, and the test material is adhered to the upper end of the second component through the pressure cover; the at least two temperature detection devices are arranged inside the second component according to the heat transfer direction of the heating element, and the second component is connected to the inner wall of the shell through a support frame.

[0009] In some embodiments, a detachable top cover is provided on the upper portion of the shell.

[0010] In some embodiments, the device further comprises an auxiliary heating coil disposed on the support frame and surrounding the test material.

[0011] In some embodiments, the device further comprises an auxiliary heating rod, and the auxiliary heating rod is disposed on the support frame.

[0012] In some embodiments, the number of the auxiliary heating rods is two, and the two auxiliary heating rods are centrally symmetrical about the center of the test material.

[0013] In some embodiments, silicone grease or liquid metal is disposed between the test material and the upper end of the heating core.

[0014] According to another aspect of the present application, a dynamic characteristics test experimental method for a zirconium alloy femtosecond laser modified surface is provided, wherein the device is applied, an ion solution is injected into the shell, and the method comprises:

[0015] Controlling the heating element to heat so that the surface solution of the test material begins to boil, and recording the current heating power of the heating element;

[0016] Controlling the heating power of the heating element to maintain the current heating power, and regularly recording the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material;

[0017] Determining a heat transfer coefficient according to the temperature value;

[0018] Determining the number of bubbles nucleated per unit area according to the bubble nucleation image;

[0019] Determining a weight change of the test material according to weight values ​​recorded in adjacent preset cycles;

[0020] The dynamic characteristics of the zirconium alloy femtosecond laser modified surface are determined based on the heat transfer coefficient, the nucleation quantity and the weight change in multiple preset cycles.

[0021] In some embodiments, the number of the temperature detection devices is three, and the three temperature detection devices arranged according to the heat transfer direction of the heating element are respectively a first temperature detection device, a second temperature detection device and a third temperature detection device; the step of determining the heat transfer coefficient according to the temperature value includes:

[0022] Determine a first heat flux density using a temperature value of the first temperature detection device, a temperature value of the second temperature detection device, a distance between the first temperature detection device and the second temperature detection device, and a thermal conductivity of the heating core;

[0023] Determine a second heat flux density using the temperature value of the second temperature detection device, the temperature value of the third temperature detection device, the distance between the second temperature detection device and the third temperature detection device, and the thermal conductivity of the heating core;

[0024] Determining the heat flux density transferred from the test material to the solution according to the first heat flux density and the second heat flux density;

[0025] Determining the temperature of the test material according to the heat flux density, the temperature value of the third temperature detection device, the distance between the third temperature detection device and the test material, and the thermal conductivity of the heating core;

[0026] The heat transfer coefficient is determined based on the thermal conductivity of the heating core, the temperature of the test material and the boiling point of the solution.

[0027] In some embodiments, the step of determining the heat flux density transferred from the test material to the solution according to the first heat flux density and the second heat flux density comprises:

[0028] An average value is calculated for the first heat flux density and the second heat flux density, and the average value is used as the heat flux density.

[0029] By means of the above technical scheme, the present application provides an experimental device and method for testing the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified. The device can provide a simulation of the real environment in which the test material is located in a nuclear reactor fuel assembly system, and determine the heat transfer coefficient, nucleation quantity and weight change of the test material by regularly acquiring the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material, thereby determining the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified including dynamic heat transfer characteristics and dirt deposition characteristics, so as to facilitate the subsequent iterative optimization of the laser modification process and evaluate the real effect of the modified surface after long-term use.

[0030] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0032] Figure 1 A schematic diagram showing the microstructure of a zirconium alloy femtosecond laser modified surface is shown as an example;

[0033] Figure 2 A front view of a dynamic characteristics test device for a zirconium alloy femtosecond laser modified surface provided in accordance with some embodiments is exemplarily shown;

[0034] Figure 3 A side view of a dynamic characteristics test device for a zirconium alloy femtosecond laser modified surface provided in accordance with some embodiments is exemplarily shown;

[0035] Figure 4 The exemplary embodiment shows the Figure 2 Schematic diagram of the AA section;

[0036] Figure 5 The exemplary embodiment shows the Figure 3 Schematic diagram of the middle BB section;

[0037] Figure 6 A flowchart of a dynamic characteristics test experimental method for a zirconium alloy femtosecond laser modified surface provided in accordance with some embodiments is exemplarily shown;

[0038] Figure 7A schematic diagram of a dynamic characteristic curve of a zirconium alloy femtosecond laser modified surface provided according to some embodiments is exemplarily shown;

[0039] Figure 8 A schematic diagram of the device structure of a computer device provided in an embodiment of the present application is shown. DETAILED DESCRIPTION

[0040] The present application will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0041] In nuclear reactor fuel assembly systems, zirconium alloys with good radiation resistance are mostly used for the cladding of nuclear fuel elements. In order to improve the local heat-carrying capacity of the nuclear reactor core, the heat transfer effect of zirconium alloys has been paid much attention. Femtosecond laser modification technology can prepare microstructures on the metal surface. Figure 1 The schematic diagram of the microstructure of a zirconium alloy femtosecond laser modified surface is shown as an example, and the geometric size of the microstructure is generally 20 to 100 μm. On the one hand, the microstructure is conducive to the increase of the contact area, and on the other hand, the microstructure can serve as a cavity for the formation of bubbles, thus having the effect of improving the heat transfer capacity.

[0042] However, in actual use, the microstructure formed by femtosecond laser is easily deposited by ions or impurities in the solution environment, causing the microstructure to gradually be filled and fail. In this dynamic process, the heat transfer performance of the femtosecond laser-modified surface will also change accordingly. Therefore, it is very important to measure the dynamic characteristics of heat transfer and dirt on the surface of zirconium alloy femtosecond laser modified surface. Therefore, how to determine the dynamic characteristics of zirconium alloy femtosecond laser modified surface has become a technical problem that needs to be solved urgently by technicians in this field.

[0043] In order to solve the above technical problems, an embodiment of the present application provides an experimental device for testing the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified, which can provide a simulation of the real environment of the test material in the nuclear reactor fuel assembly system, and determine the heat transfer coefficient, nucleation quantity and weight change of the test material by regularly obtaining the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material, thereby determining the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified including dynamic heat transfer characteristics and dirt deposition characteristics, so as to facilitate the subsequent iterative optimization of the laser modification process and evaluate the real effect of the modified surface after long-term use.

[0044] The present invention provides a dynamic characteristics test device for a zirconium alloy femtosecond laser modified surface. Figure 2A front view of an experimental device for testing dynamic properties of a zirconium alloy femtosecond laser modified surface provided in accordance with some embodiments is exemplarily shown. Figure 3 A side view of an experimental device for testing dynamic characteristics of a zirconium alloy femtosecond laser modified surface provided according to some embodiments is exemplarily shown. Figure 4 The exemplary embodiment shows the Figure 2 Schematic diagram of the AA section.

[0045] The device comprises: a housing 1, a support frame 2, a heating component 3 and a pressure cover 4, wherein the support frame 2, the heating component 3 and the pressure cover 4 are located inside the housing 1. Exemplarily, the material of the housing 1 can be stainless steel.

[0046] The heating assembly 3 includes a heating core 31 and a heating element 32. The material of the heating core can be a material with strong thermal conductivity, and can be copper for example. The heating element 32 can be an electric heating rod. The heating element is arranged inside the heating core, and a test material is arranged on the upper end of the heating core, and the test material is attached to the upper end of the heating core through the gland. The test material is a zirconium alloy femtosecond laser modified material.

[0047] In an embodiment of the present application, before the experiment, an ion solution is injected into the shell. An exemplary ion solution may be a solution containing Fe ions or Ni ions. Then, the heating element is energized. After energization, the heating element starts to heat and transfers heat to the surface of the test material through the heating core. Then, the temperature of the solution in contact with the surface of the test material will gradually increase. Finally, the solution will reach a boiling state due to surface heating, and the dynamic properties of the zirconium alloy femtosecond laser modified surface are tested in the boiling state.

[0048] At least two temperature detection devices are arranged in the heating core and between the heating element and the test material according to the heat transfer direction of the heating element. The temperature detection device may be a thermocouple.

[0049] The dynamic characteristics tested in the embodiments of the present application include dynamic heat transfer characteristics. Specifically, the heat transfer coefficient of the test material can be determined by the temperature data of the temperature detection device, and the dynamic heat transfer characteristics can be characterized by the heat transfer system. During the experiment, the heating element starts heating after being connected to the power supply and conducts heat to the surface of the test material through the heating core. Therefore, the heat transfer direction of the heating element in the embodiments of the present application includes the direction in which the heating element transfers heat to the test material.

[0050] In some embodiments, the heating core 31 includes a first component 311 and a second component 312 connected to the first component 311. In some embodiments, the first component 311 and the second component 312 are an integrally formed structure.

[0051] The heating element 32 is disposed in the first component 311. In some embodiments, a hole is disposed inside the first component 311, and the heating element 32 is disposed in the hole. Specifically, the conducting part 321 of the heating element 32 is located outside the hole, and the rest of the heating element 32 is located inside the hole and is in contact with the inner wall of the hole.

[0052] The test material is arranged on the upper end of the second component, and the test material is attached to the upper end of the second component through the gland. The second component 312 is connected to the inner wall of the housing 1 through the support frame 2, and the support frame 2 plays a supporting and fixing role.

[0053] In some embodiments, Figure 5 The exemplary embodiment shows the Figure 3 Schematic diagram of the BB section in the figure. The gland can be an annular structure, which includes an inner circle and an outer circle. The inner circle contacts the edge of the test material so that the test material is fixed to the upper end of the second component through the gland. In one example, the shape of the test material is circular, and the diameter of the inner circle can be the same as the diameter of the test material. Of course, the diameter of the inner circle can be smaller than the diameter of the test material. At this time, the edge of the test material is covered by the gland. It should be noted that the test material needs to retain a part that will not be covered by the gland, because before the experiment, the shell 1 needs to be filled with an ion solution. During the experiment, the ion solution is in contact with the heated test material, so that the dynamic characteristics of the test material can be obtained, so the test material must be at least partially exposed to the solution. The outer circle is tightly matched with the support frame, and finally the gland is tightly fixed on the support frame. It can be understood that the support frame has a structure that is tightly matched with the outer circle, and the specific structure can be a groove that matches the outer circle. In addition, in addition to playing the role of making the test material and the upper end of the heating core fit tightly, the gland can also ensure that the solution does not leak downward, that is, it ensures that the solution only contacts the upper surface of the test material and does not flow to the side wall of the test material. At least two temperature detection devices 3121 are arranged inside the second component according to the heat transfer direction of the heating element.

[0054] In some embodiments, the number of temperature detection devices is three. Figure 4 ,exist Figure 4 In the figure, heat is transferred from the heating element 32 to the test material 5. From the figure, the heat transfer direction is from bottom to top, so the three temperature detection devices 3121 are arranged from bottom to top inside the heating core.

[0055] In some embodiments, silicone grease or liquid metal is disposed between the test material and the upper end of the heating core. The silicone grease or liquid metal can fill the gap between the test material and the upper end of the heating core, thereby enhancing the thermal conductivity of the test material and the heating core.

[0056] In the embodiment of the present application, a visual window 6 is provided on the shell, and the visual range of the visual window includes the test material. In the embodiment of the present application, the visual window can be used to capture the bubble nucleation image of the test material, and the number of nucleations in the bubble nucleation image can be counted. The number of nucleations refers to the number of bubbles formed on the part of the test material in contact with the solution when the solution in contact with the test material boils. The number of nucleations can also be used to characterize dynamic heat transfer characteristics.

[0057] In some embodiments, a removable top cover 7 is provided on the upper part of the housing. Before the experiment, the removable top cover can be removed, the test material is placed on the upper end of the heating core, and then the test material and the upper end of the heating core are tightly fitted using a pressure cap. The solution is poured into the housing, and the removable top cover is reinstalled on the upper part of the housing.

[0058] In some embodiments, the device further comprises an auxiliary heating coil 8, which is disposed on the support frame and around the test material. In some embodiments, the device further comprises an auxiliary heating rod 9, which is disposed on the support frame.

[0059] Before the experiment, while controlling the heating of the heating elements, the auxiliary heating coils and / or auxiliary heating rods are also controlled for heating. When the solution in contact with the test material boils, the heating power of the auxiliary heating coils and the auxiliary heating rods is recorded, and the heating power is maintained during the subsequent experiments. In this way, the temperature of the solution can be maintained by the auxiliary heating coils and the auxiliary heating rods.

[0060] In some embodiments, the number of the auxiliary heating rods is two, and the two auxiliary heating rods are centrally symmetrical about the center of the test material, so as to better maintain the temperature of the solution around the test material.

[0061] The embodiment of the present application also provides a dynamic characteristics test experimental method for the surface of zirconium alloy modified by femtosecond laser, using the device, an ion solution is injected into the shell.

[0062] Figure 6 The flowchart of a dynamic characteristic test experimental method of a zirconium alloy femtosecond laser modified surface according to some embodiments is exemplarily shown. The method includes S100-S600.

[0063] S100, controlling the heating element to heat so that the surface solution of the test material begins to boil, and recording the current heating power of the heating element.

[0064] Before executing step S100, first complete the overall assembly of the device, then assemble the test material in the device, and install the gland. Inject a certain concentration of ion solution into the shell through the top cover. Then execute step S100. In the embodiment of the present application, after the heating element is heated, the heat is transferred to the test material through the heating core, and then the surface solution temperature of the test material will also increase, and finally reach a boiling state, at which time the current heating power of the heating element is recorded.

[0065] S200, controlling the heating power of the heating element to maintain the current heating power, and regularly recording the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material. In the embodiment of the present application, controlling the heating power of the heating element to maintain the current heating power can keep the solution in contact with the surface of the test material in a boiling state, so as to simulate the real environment of the test material with a zirconium alloy femtosecond laser modified surface in a nuclear reactor fuel assembly system.

[0066] In some embodiments, the preset period may be 3-5 days, during which the temperature values ​​of at least two temperature detection devices may be recorded regularly and bubble nucleation images may be captured. In addition, the weight value of the test material may be recorded at the end of a preset period.

[0067] After a preset cycle, the heating power of the heating element, the auxiliary heating rod and the auxiliary heating coil can be gradually reduced to finally cut off the power. When the temperature of the ion solution is low, that is, when it reaches a certain temperature, the ion solution can be discharged from the housing, and the test material can be taken out and weighed. In some embodiments, each time the test material is weighed, the test material can be taken out from the detachable top cover and weighed.

[0068] Then the experiment of the next preset cycle can be continued. In the experiment of the next preset cycle, the solution discharged from the shell will continue to be added into the shell. The heating power of the heating components, auxiliary heating rods and auxiliary heating coils used in addition also needs to be the same as the heating power used in the previous preset cycle test experiment. By obtaining the temperature values ​​of at least two temperature detection devices recorded in multiple preset cycles, the bubble nucleation image of the surface of the test material photographed through the visual window and the weight value of the test material, the dynamic heat transfer characteristics and dirt deposition characteristics are determined, thereby obtaining dynamic characteristic changes. During the experiment, it is necessary to ensure that the ion concentration of the ion solution in each preset cycle remains unchanged. Specifically, the ion solubility in the solution can be detected every day, and the ion concentration can be ensured to remain unchanged by adding solutes and other methods.

[0069] S300: Determine a heat transfer coefficient according to the temperature value. In the embodiment of the present application, the heat transfer coefficient can characterize the dynamic heat transfer characteristics of the surface of the test material.

[0070] In some embodiments, the number of the temperature detection devices is three, and the three temperature detection devices arranged according to the heat transfer direction of the heating element are respectively a first temperature detection device, a second temperature detection device and a third temperature detection device; the step of determining the heat transfer coefficient according to the temperature value includes:

[0071] The first heat flux density is determined by using the temperature value of the first temperature detection device, the temperature value of the second temperature detection device, the distance between the first temperature detection device and the second temperature detection device, and the thermal conductivity of the heating core. Specifically, the first heat flux density can be calculated using the following formula:

[0072]

[0073] Among them, q1 is the first heat flux, k c is the thermal conductivity of the heating core, T1 is the temperature value of the first temperature detection device, T2 is the temperature value of the second temperature detection device, and Z1 is the distance between the first temperature detection device and the second temperature detection device.

[0074] The second heat flux density is determined by using the temperature value of the second temperature detection device, the temperature value of the third temperature detection device, the distance between the second temperature detection device and the third temperature detection device, and the thermal conductivity of the heating core. Specifically, the second heat flux density can be calculated using the following formula:

[0075]

[0076] Where q2 is the second heat flux, k cis the thermal conductivity of the heating core, T3 is the temperature value of the third temperature detection device, T2 is the temperature value of the second temperature detection device, and Z2 is the distance between the second temperature detection device and the third temperature detection device.

[0077] According to the first heat flux density and the second heat flux density, the heat flux density transferred from the test material to the solution is determined; in some embodiments, the step of determining the heat flux density transferred from the test material to the solution according to the first heat flux density and the second heat flux density includes: averaging the first heat flux density and the second heat flux density, and taking the average value as the heat flux density. Specifically, the heat flux density can be calculated using the following formula:

[0078]

[0079] Among them, q is the heat flux density, q1 is the first heat flux density, and q2 is the second heat flux density.

[0080] The temperature of the test material is determined according to the heat flux density, the temperature value of the third temperature detection device, the distance between the third temperature detection device and the test material, and the thermal conductivity of the heating core. Specifically, under the heat preservation measures, when it is assumed that there is no heat loss from the temperature detection device to the surface of the test material, the temperature of the test material can be calculated according to the following formula:

[0081]

[0082] Among them, T w is the temperature of the test material, T3 is the temperature value of the third temperature detection device, q is the heat flux density, L is the distance between the third temperature detection device and the test material, k c is the thermal conductivity of the heating core.

[0083] The heat transfer coefficient is determined based on the thermal conductivity of the heating core, the temperature of the test material and the boiling point of the solution. Specifically, the heat transfer coefficient can be calculated based on Newton's cooling formula:

[0084]

[0085] Where h is the heat transfer coefficient, q is the heat flux, T w is the temperature of the test material, T s is the boiling point of the solution. For water, at room pressure, T s is 100°C.

[0086] S400. Determine the number of bubble nucleations per unit area according to the bubble nucleation image. For femtosecond laser modified surfaces, since the ions in the ionic solution are continuously deposited on the microstructure of the surface of the test material, the area of ​​contact between the surface of the test material and the solution will continuously change, so that the heat transfer coefficient h will change; at the same time, the microstructure is continuously filled with dirt, resulting in a continuous decrease in the number of forming points of boiling bubbles, which leads to a change in the number of nucleations. Therefore, in the embodiment of the present application, the dynamically changing number of nucleations and the heat transfer coefficient are calculated to evaluate its dynamic heat transfer characteristics.

[0087] Specifically, the number of nucleations per unit area can be calculated according to the following formula:

[0088]

[0089] Where Na is the number of nucleations per unit area, N is the number of bubbles attached to the surface of the test material in the bubble nucleation image, and S is the area of ​​the test material.

[0090] S500: Determine the weight change of the test material according to the weight values ​​recorded in adjacent preset cycles.

[0091] In the embodiments of the present application, the change in the dirt deposition characteristics and the change in the heat transfer characteristics occur at the same time. As the bubbles continue to boil on the surface of the test material, the ions in the solution will undergo chemical changes such as oxidation to form water-insoluble precipitates that adhere to the microstructure of the femtosecond laser-modified surface. Therefore, the dirt deposition characteristics are characterized by the weight change of the test material.

[0092] In the embodiment of the present application, during the experiment, the ion concentration of the solution in the shell is kept constant, and when the ion concentration is found to decrease, the solute needs to be replenished in time. As the microstructure on the surface of the test material increases with the time of immersion in the solution, the microstructure is easily deposited by ions or impurities in the solution environment, causing the microstructure to gradually be filled and ineffective. The dynamic characteristics in the embodiment of the present application also include dynamic dirt deposition characteristics. The weight change of the test material in adjacent preset cycles can be used to evaluate the degree of dirt deposition on the surface of the test material and characterize the dynamic dirt deposition characteristics of the zirconium alloy femtosecond laser modified surface. Therefore, the weight values ​​recorded in multiple preset cycles are calculated here, and the weight values ​​recorded in two adjacent preset cycles are subtracted to obtain the weight change of the test material.

[0093] S600, determining the dynamic characteristics of the zirconium alloy femtosecond laser modified surface according to the heat transfer coefficient, the nucleation quantity and the weight change of multiple preset cycles.

[0094] Figure 7 The following is a schematic diagram of a dynamic characteristic curve of a zirconium alloy femtosecond laser modified surface according to some embodiments. Figure 7 In the figure, the red data points are the heat transfer coefficient h, the red data points are the nucleation number Na per unit area, and the blue data points are the weight change of the test material. For the femtosecond laser modified surface, as the test experiment continues, more and more dirt is deposited, which will lead to a decrease in the surface heat transfer capacity of the test material. Based on the regularly obtained heat transfer coefficient h, the nucleation number Na per unit area, and the weight change Δw, a curve can be drawn, such as Figure 7 As shown, Figure 7 The unit of the horizontal axis is day.

[0095] The method in the embodiments of the present application can evaluate the dynamic changes of the heat transfer characteristics and the dirt deposition characteristics of the modified surface, and can be used to analyze the mutual influence of dirt deposition and heat transfer on the modified surface under real environment, guide the iterative optimization of the laser modification process, and evaluate the real effect of the modified surface after long-term use.

[0096] By means of the above technical scheme, the present application provides an experimental device and method for testing the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified. The device can provide a simulation of the real environment in which the test material is located in a nuclear reactor fuel assembly system, and determine the heat transfer coefficient, nucleation quantity and weight change of the test material by regularly acquiring the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material, thereby determining the dynamic characteristics of the surface of zirconium alloy femtosecond laser modified including dynamic heat transfer characteristics and dirt deposition characteristics, so as to facilitate the subsequent iterative optimization of the laser modification process and evaluate the real effect of the modified surface after long-term use.

[0097] The present application also provides a computer device, which may be a personal computer, a server, a network device, etc. Figure 8 As shown, the computer device includes a bus, a processor, a memory and a communication interface, and may also include an input and output interface and a display device. Among them, the processor of the computer device is used to provide computing and control capabilities. The memory of the computer device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system, a computer program and a database. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The database of the computer device is used to store location information. The network interface of the computer device is used to communicate with an external terminal through a network connection. When the computer program is executed by the processor, the steps in each method embodiment are implemented.

[0098] Those skilled in the art will understand that Figure 8The structure shown in the figure is only a block diagram of a part of the structure related to the solution of the present application, and does not constitute a limitation on the computer device to which the solution of the present application is applied. The specific computer device may include more or fewer components than those shown in the figure, or combine certain components, or have a different arrangement of components.

[0099] In one embodiment, a computer-readable storage medium is provided. The computer-readable storage medium may be non-volatile or volatile, and stores a computer program thereon. When the computer program is executed by a processor, the steps in the above-mentioned method embodiments are implemented.

[0100] In one embodiment, a computer program product is provided, including a computer program, which implements the steps in the above method embodiments when executed by a processor.

[0101] It should be noted that the user information (including but not limited to user device information, user personal information, etc.) and data (including but not limited to data used for analysis, stored data, displayed data, etc.) involved in this application are all information and data authorized by the user or fully authorized by all parties.

[0102] Those skilled in the art can understand that all or part of the processes in the above-mentioned embodiment methods can be completed by instructing the relevant hardware through a computer program, and the computer program can be stored in a non-volatile computer-readable storage medium. When the computer program is executed, it can include the processes of the embodiments of the above-mentioned methods. Among them, any reference to the memory, database or other medium used in the embodiments provided in the present application can include at least one of non-volatile and volatile memory. Non-volatile memory can include read-only memory (ROM), magnetic tape, floppy disk, flash memory, optical memory, high-density embedded non-volatile memory, resistive random access memory (ReRAM), magnetoresistive random access memory (MRAM), ferroelectric random access memory (FRAM), phase change memory (PCM), graphene memory, etc. Volatile memory can include random access memory (RAM) or external cache memory, etc. As an illustration and not limitation, RAM can be in various forms, such as static random access memory (SRAM) or dynamic random access memory (DRAM). The database involved in each embodiment provided in this application may include at least one of a relational database and a non-relational database. Non-relational databases may include distributed databases based on blockchains, etc., but are not limited to this. The processor involved in each embodiment provided in this application may be a general-purpose processor, a central processing unit, a graphics processor, a digital signal processor, a programmable logic device, a data processing logic device based on quantum computing, etc., but are not limited to this.

[0103] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0104] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An experimental device for testing dynamic characteristics of zirconium alloy femtosecond laser modified surface, characterized in that: include: A shell, a support frame, a heating component and a gland, wherein the support frame, the heating component and the gland are located inside the shell; The heating assembly comprises a heating core and a heating element, wherein the heating element is arranged inside the heating core, a test material is arranged on the upper end of the heating core, and the test material is attached to the upper end of the heating core through the gland; at least two temperature detection devices are arranged inside the heating core and between the heating element and the test material according to the heat transfer direction of the heating element; the heating core is connected to the shell through the support frame; The housing is provided with a visual window, and the visual range of the visual window includes the test material.

2. The device according to claim 1, characterized in that The heating core includes a first component and a second component connected to the first component, and the heating element is arranged in the first component; the test material is arranged at the upper end of the second component, and the test material is attached to the upper end of the second component through the pressure cover; the at least two temperature detection devices are arranged inside the second component according to the heat transfer direction of the heating element, and the second component is connected to the inner wall of the shell through a support frame.

3. The device according to claim 1, characterized in that A detachable top cover is arranged on the upper part of the shell.

4. The device according to claim 1, characterized in that The device also includes an auxiliary heating coil, which is disposed on the support frame and around the test material.

5. The device according to claim 1, characterized in that It also includes an auxiliary heating rod, which is arranged on the supporting frame.

6. The device according to claim 5, characterized in that The number of the auxiliary heating rods is two, and the two auxiliary heating rods are centrally symmetrical about the center of the test material.

7. The device according to claim 1, characterized in that Silicone grease or liquid metal is arranged between the test material and the upper end of the heating core.

8. An experimental method for testing dynamic characteristics of a zirconium alloy femtosecond laser modified surface, using the device of claim 1, characterized in that: An ion solution is injected into the shell, and the method comprises: Controlling the heating element to heat so that the surface solution of the test material begins to boil, and recording the current heating power of the heating element; Controlling the heating power of the heating element to maintain the current heating power, and regularly recording the temperature values ​​of at least two temperature detection devices within a preset period, regularly photographing the bubble nucleation image of the surface of the test material through the visual window, and recording the weight value of the test material; Determining a heat transfer coefficient according to the temperature value; Determining the number of bubbles nucleated per unit area according to the bubble nucleation image; Determining a weight change of the test material according to weight values ​​recorded in adjacent preset cycles; The dynamic characteristics of the zirconium alloy femtosecond laser modified surface are determined based on the heat transfer coefficient, the nucleation quantity and the weight change in multiple preset cycles.

9. The method according to claim 8, characterized in that The number of the temperature detection devices is three, and the three temperature detection devices arranged according to the heat transfer direction of the heating element are respectively a first temperature detection device, a second temperature detection device and a third temperature detection device; The step of determining the heat transfer coefficient according to the temperature value comprises: Determine a first heat flux density using a temperature value of the first temperature detection device, a temperature value of the second temperature detection device, a distance between the first temperature detection device and the second temperature detection device, and a thermal conductivity of the heating core; Determine a second heat flux density using the temperature value of the second temperature detection device, the temperature value of the third temperature detection device, the distance between the second temperature detection device and the third temperature detection device, and the thermal conductivity of the heating core; Determining the heat flux density transferred from the test material to the solution according to the first heat flux density and the second heat flux density; Determining the temperature of the test material according to the heat flux density, the temperature value of the third temperature detection device, the distance between the third temperature detection device and the test material, and the thermal conductivity of the heating core; The heat transfer coefficient is determined based on the thermal conductivity of the heating core, the temperature of the test material and the boiling point of the solution.

10. The method according to claim 9, characterized in that The step of determining the heat flux density transferred from the test material to the solution according to the first heat flux density and the second heat flux density comprises: An average value is calculated for the first heat flux density and the second heat flux density, and the average value is used as the heat flux density.

Citation Information

Patent Citations

  • Refractory material heat transfer performance testing device and application method thereof

    CN107576684A

  • Pool inside boiling heat transfer experimental device for high heat flow density micro-nano structure surface

    CN108872298A

  • On-line measuring device and method for density of ultrahigh-temperature molten working medium

    CN111883272A

  • Test system and method for testing combustion risk of magnesium alloy

    CN112034004A

  • Visual pool boiling experiment system and working method thereof

    CN113218990A